Communal biofuel burning for district heating: Emissions and immissions from medium-sized (0.4 and 1.5 MW) facilities. (May 2018) - Fachinger, Friederike; Drewnick, Frank; Gieré, Reto; Borrmann, Stephan
Abstract: Particulate and gaseous emissions of two medium-sized district heating facilities (400 kW, fueled with miscanthus, and 1.5 MW, fueled with wood chips) were characterized for different operational conditions, and compared to previously obtained results for household wood and pellet stoves. SO2 and NOx emission factors (reported in mg MJFuel −1 ) were found to not only depend on fuel sulfur/nitrogen content, but also on combustion appliance type and efficiency. Emission factors of SO2, NOx, and PM (particulate matter) increased with increasing load. Particle chemical composition did not primarily depend on operational conditions, but varied mostly with combustion appliances, fuel types, and flue gas cleaning technologies. Black carbon content was decreasing with increasing combustion efficiency; chloride content was strongly enhanced when burning miscanthus. Flue gas cleaning using an electrostatic precipitator caused strong reduction not only in total PM, but also in the fraction of refractory and semi-refractory material within emitted PM1 . For the impact of facilities on their surroundings (immissions) not only their total emissions are decisive, but also their stack heights. In immission measurements downwind of the two facilities, a plume could only be observed for the 400 kW facility with low (11 m) stack height (1.5 MW facility: 30 m), and measured immissions agreed reasonably well with predicted ones. The impact of these immissions is non-negligible: At a distance of 50 m from the facility, apart from CO2, also plume contributions of NOx, ultrafine particles, PM1, PM10, poly-aromatic hydrocarbons, and sulfate were detected, with enhancements above background values of 2–130%. Highlights: Midsized biofuel heating plants' emission factors depend on load and operational mode. Flue gas cleaning with electrostatic precipitator changes composition of emitted PM. Emission factors and stack height are decisive for immissions around facility. Central biomass burning facilities with high stack preferable to household stoves.